Pola Pemberdayaan Zakat Badan Amil Zakat Nasional (BAZNAS) Terhadap Masyarakat Miskin Pesisir Pantai Ampenan Kota Mataram - Rina Margasari; Muh. Salahuddin; Baiq Ratna Mulhimmah (Journal of Management and Bussines (JOMB), 2023)
This research aims at the mechanism for empowering the Mataram City BAZ zakat towards the poor coastal communities of Ampenan and to analyze the economic impact of the poor coastal communities of Ampenan on empowering the zakat provided by the Mataram City BAZ. The type of research used is qualitative with research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior. The results of this research show that the first Empowerment Pattern of zakat funds carried out by BAZNAS Mataram City is distributed through 5 patterns to mustahik in the form of consumptive zakat and productive zakat such as (1) Mataram Peduli Program (2) Mataram Takwa Program (3) Smart Mataram Program. (4) Healthy Mataram Program. Productive zakat is distributed through (5) Mataram Sejahtera Programs. Conclusion, secondly, the economic impact of zakat can improve the welfare of mustahiq and some mustahiq who have not been able to improve their standard of living because the funds provided are too minimal. There are 345 poor people on the Ampenan coast who have been helped. With the help of these zakat funds, people are able to survive amidst their lower middle class economic conditions and become middle class. Of the total 345 mustahik who received zakat assistance, there was an increase in the change of 0.40% from mustahik to muzzaki. Keywords: Poverty, Empowerment, Zakat